2020
DOI: 10.1080/00063657.2020.1734534
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of non-breeding Eurasian Griffon VulturesGyps fulvusin relation to natural and artificial food availability

Abstract: Capsule: The movements and spatial ecology of non-breeding Eurasian Griffon Vultures Gyps fulvus in northern Italy, Croatia and Austria do not seem to be affected by feeding station use. Aims: The purpose of this study was to assess how the creation of a feeding station at the Riserva Naturale Regionale del Lago di Cornino (Forgaria nel Friuli, northeast Italy) during the 1980s might have affected the spatial and behavioural ecology of the Eurasian Griffon Vulture. Methods: Using global positioning system (GPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 79 publications
1
17
2
Order By: Relevance
“…In Italy, the spring core area (equivalent to the basic area in our study) was significantly smaller than in summer [49], while in Croatia the largest core area was recorded during the autumn, but no significant difference between seasons was detected [49]. These results also suggest that vultures tended to stay more within their respective areas in autumn than in spring and/or summer when flight conditions are less favorable [49,54]. Our results are in accordance with studies from Bulgaria [32] and France [45], as we also observed smaller foraging ranges, home ranges and basic areas during winter and autumn.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In Italy, the spring core area (equivalent to the basic area in our study) was significantly smaller than in summer [49], while in Croatia the largest core area was recorded during the autumn, but no significant difference between seasons was detected [49]. These results also suggest that vultures tended to stay more within their respective areas in autumn than in spring and/or summer when flight conditions are less favorable [49,54]. Our results are in accordance with studies from Bulgaria [32] and France [45], as we also observed smaller foraging ranges, home ranges and basic areas during winter and autumn.…”
Section: Discussioncontrasting
confidence: 54%
“…Smaller basic, core, home and foraging ranges were also noticeable during the autumn of 2013 and winter of 2013/2014. In Italy, the spring core area (equivalent to the basic area in our study) was significantly smaller than in summer [49], while in Croatia the largest core area was recorded during the autumn, but no significant difference between seasons was detected [49]. These results also suggest that vultures tended to stay more within their respective areas in autumn than in spring and/or summer when flight conditions are less favorable [49,54].…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…It is shared amongst Croatia, Italy, Slovenia and Austria (see Fig. 4 ) with several centres - Lago di Cornino Nature Reserve ( N46.22, E13.02 , Italy), where Griffon Vulture has been re-introduced and started breeding in the 1990s ( Mihelic and Genero 2005 ), the Kvarner Archipelago (North Adriatic) - islands of Cres, Krk, Plavnik, Prvich and Pag ( N44.98, E14.40 , Croatia), Hohe Tauern National Park ( N47.14, E12.85 , Austria) with some extentions towards the Triglav National Park ( N46.36, E13.55 , Slovenia) - also reported by Mihelic and Genero (2005) and Genero et al (2020) . The 50% core area of the zone is 291.37 km 2 and the 95% home range is calculated at 6,803.04 km 2 (based on the location data of three tracked birds).…”
Section: Resultsmentioning
confidence: 59%
“…comm. ), but also published studies ( Genero et al 2020 ), additional research is necessary. A vulture feeding site was operating regularly in Lago di Cornino National Park, Italy and occasionally on the Island of Cres, Croatia, throughout the study period.…”
Section: Resultsmentioning
confidence: 99%